Analisis Strategis Dan Dampak Ekonomi Multinasional Company (MNC) Di PT Unilever Indonesia TBK - Zahra Nur Maulidia; Daspar Daspar (Jurnal Ekonomi dan Bisnis Digital, 2026)
This paper discusses the strategic analysis and economic impact of a Multinational Corporation (MNC), focusing on PT Unilever Indonesia Tbk as one of the leading fast-moving consumer goods (FMCG) companies in Indonesia. The study employs a descriptive approach based on literature review and analysis of the company’s profile, expansion motives from the perspective of international business theory, and its economic contributions to the host country, Indonesia. The findings indicate that PT Unilever Indonesia Tbk’s expansion is driven by market-seeking, efficiency-seeking, resource-seeking, and strategic asset-seeking motives. The company contributes positively to the Indonesian economy through employment generation, foreign investment, tax payments, support for small and medium enterprises (SMEs) and distribution networks, technology transfer, and the development of the manufacturing sector. At the same time, the company faces various global challenges, including intense market competition, changing consumer preferences, digital transformation, and increasing demands for environmental sustainability. Therefore, adaptive and innovative business strategies are essential for maintaining the company’s competitiveness while continuing to provide economic benefits to Indonesia..